Styrenated sunflower oil polymers from raft process for coating application - Alemdar, Neslihan; Erciyes, A. Tuncer; Bicak, Niyazi (Wiley, 2011)
AbstractOil‐based macroinitiator (MI) obtained from sunflower oil was styrenated using reversible addition–fragmentation chain transfer polymerization (RAFT) in the presence of phenacyl morpholine dithiocarbamate (PMDC) as chain transfer agent. The solvent effect and effect of the molar ratio of the transfer agent, PMDC, on polydispersity and molecular weight of the polymers were investigated. The obtained results showed that, 1,4‐dioxane is a better solvent and 1/4 molar ratio of [MI]/[PMDC] provides relatively low polydispersities. No homopolystyrene was detected under these conditions, indicating the efficiency of PMDC in the chain transfer process. Livingness of the polymerization process was confirmed by chain extension with styrene using the preformed polymer as macrotransfer agent. The film properties of styrenated oil samples were determined according to the related standards. To improve film properties, the polymer obtained by RAFT technique was modified by reaction with MI. The resulting material gave transparent films with good film properties. © 2011 Wiley Periodicals, Inc. J Appl Polym Sci, 2012